2006
DOI: 10.1007/s10826-006-9111-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Screening of Female Juvenile Offenders: Replication of a Subtyping Strategy

Abstract: Recent research indicates that adjudicated female youth have higher rates of mental health problems and histories of trauma exposure and abuse relative to adjudicated male youth. These differences are important for gender-specific assessment, intervention, and management strategies. We replicated a subtyping strategy for adjudicated female youth based on mental health screening data from the Massachusetts Youth Screening Instrument-2 (MAYSI-2) by investigating subtype differences on trauma symptoms, abuse hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…As a final limitation, this study was conducted with a school sample of adolescents and thus may not be generalizable to younger children, at-risk youth, or youth who exhibit severe behavioral and=or emotional problems. However, given the past associations found between other types of trauma (e.g., abuse, community violence) and emotionally dysregulated aggressive reactions (e.g., Connor et al, 2003;Shields & Cicchetti, 1998Steiner et al, 1997), it seems likely that this model would be applicable to youth exposed to a wide range of traumatic events as well as to justice-involved youth who consistently report high rates of trauma (Cauffman et al, 1998;Cruise et al, 2007;Wood et al, 2002). Further, younger children's emotional responses to natural disasters (e.g., Scheeringa & Zeanah, 2008;Vernberg et al, 1996) and tendencies to display emotional regulation problems and reactive aggression related to maltreatment or abuse (Connor et al, 2003;Shields & Cicchetti, 1998 suggest that the current results would also be applicable to youth in general and not limited to adolescents only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final limitation, this study was conducted with a school sample of adolescents and thus may not be generalizable to younger children, at-risk youth, or youth who exhibit severe behavioral and=or emotional problems. However, given the past associations found between other types of trauma (e.g., abuse, community violence) and emotionally dysregulated aggressive reactions (e.g., Connor et al, 2003;Shields & Cicchetti, 1998Steiner et al, 1997), it seems likely that this model would be applicable to youth exposed to a wide range of traumatic events as well as to justice-involved youth who consistently report high rates of trauma (Cauffman et al, 1998;Cruise et al, 2007;Wood et al, 2002). Further, younger children's emotional responses to natural disasters (e.g., Scheeringa & Zeanah, 2008;Vernberg et al, 1996) and tendencies to display emotional regulation problems and reactive aggression related to maltreatment or abuse (Connor et al, 2003;Shields & Cicchetti, 1998 suggest that the current results would also be applicable to youth in general and not limited to adolescents only.…”
Section: Discussionmentioning
confidence: 99%
“…This body of work has consistently shown that youth who are abused or exposed to other forms of violence exhibit higher rates of disruptive behavior problems, often with accompanying PTSD symptoms (see also Ford, 2002;Wood et al, 2002, for reviews). In support of this association, results from numerous studies with antisocial or delinquent youth indicate that, in general, these youth have high rates of both trauma histories and posttraumatic stress symptoms (Cauffman, Feldman, Waterman, & Steiner, 1998;Cruise, Marsee, Dandreaux, & DePrato, 2007;Wood et al, 2002).…”
mentioning
confidence: 92%
“…In line with these results, delinquent female teenagers present a longer history of mistreatment, abuse and/or children exploitation, which leads to low self-esteem and accumulation of risks to commit more criminal acts. The personality of young female offenders presents a dual functioning, coexisting styles linked to transgression alongside others related to affliction and emotional vulnerability (Cruise, Marsee, Dandreaux and DePrato, 2007;Stefurak and Calhoun, 2007;Vinet and Alarcón, 2009). Furthermore, the group has shown a low control of impulses and a low suggestibility in contrast with nonviolent adolescents (Stephenon, Woodhams and Cooke, 2014).…”
Section: Topic Developmentmentioning
confidence: 99%
“…Adolescent females have been found to use substances as a way to selfmedicate in an effort to numb the evasive pain of their traumatic experiences (Quinn et al, 2005). Trauma is also known to predispose adolescent females to aggressive and antisocial behaviors (Cruise, Marsee, Dandreaux, & DePrato, 2007).…”
Section: Childhood Traumamentioning
confidence: 99%